Social Choice Theory and the Informational Basis Approach. - Roberts, K (Department of Economics (University of Oxford), 2005)
For over a quarter of a century, the use of utility information based upon interpersonal comparisons has been seen as an escape route from the Arrow Impossibility Theorem. This paper critically examines this informational basis approach to social choice. Even with comparability of differences and levels, feasible social choice rules must be insensitive to a range of distributional issues. Also, the Pareto principle is not solely to blame for the inability to adopt rules combining utility and non-utility information: if the Pareto principle is not invoked then there is no way of combining utility and non-utility information in a ranking of states unless levels of utility are comparable; with level comparability, information can be combined only in restrictive ways and the notion of giving different independent weight to different considerations is ruled out. If informational bases are viewed as the restriction on information that is available, rather than a theoretical limit on information, then there exist methods to estimate richer informational structures and overcome these difficulties.